Treatment of asphyxiated newborns with moderate hypothermia in routine clinical practice: how cooling is managed in the UK outside a clinical trial. Issue 4 (5th December 2008) - Azzopardi, D; Strohm, B; Edwards, A D; Halliday, H; Juszczak, E; Levene, M; Thoresen, M; Whitelaw, A; Brocklehurst, P
Abstract : Background: This is a phase 4 study of infants registered with the UK TOBY Cooling Register from December 2006 to February 2008. The registry was established on completion of enrolment to the TOBY randomised trial of treatment with whole body hypothermia following perinatal asphyxia at the end of November 2006. Methods: We collected information about patient characteristics, condition at birth, resuscitation details, severity of encephalopathy, hourly temperature record, clinical complications and outcomes before hospital discharge. Results: 120 infants born at a median of 40 (IQR 38–41) weeks' gestation and weighing a median of 3287 (IQR 2895–3710) g at birth were studied. Cooling was started at a median of 3 h 54 min (IQR 2 h–5 h 32 min) after birth. All but three infants underwent whole body cooling. The mean (SD) rectal temperature from 6 to 72 h of the cooling period was 33.57°C (0.51°C). The daily encephalopathy score fell: median (IQR) 11 (6–15), 9.7 (5–14), 8 (5–13) and 7 (2–12) on days 1–4 after birth, respectively. 51% of the infants established full oral feeding at a median (range) of 9 (4–24) days. 26% of the study infants died. MRI was consistent with hypoxia-ischaemia in most cases. Clinical complications were not considered to be due to hypothermia. Conclusion: In the UK, therapeutic hypothermia following perinatal asphyxia is increasingly being provided. The target body temperature is successfully achieved and the clinical complications observed were not attributed to hypothermia. Treatment with hypothermia may have prevented the worsening of the encephalopathy that is commonly observed following asphyxia.